Experimental Evaluation of a Novel Thermodynamic Inhibitor for CH4 and CO2 Hydrates. (2016) - Khan, Muhammad Saad; Lal, Bhajan; Partoon, Behzad; Keong, Lau Kok; Bustam, Azmi B.; Mellon, Nurhayati Bt
Abstract: In natural gas transmission and processing, gas hydrate formation is a major flow assurance challenge which led scientists towards conducting new and more detailed studies on different aspects of gas hydrates inhibitors. Ionic liquids (IL) recently revealed as novel hydrate inhibitors due to their unique properties like electrostatic charges together with ability to form hydrogen bonding with water molecule lead them viable research area in the field of gas hydrate mitigation. This paper highlighted the experimental evaluation of thermodynamic measurements of tetra methyl ammonium hydroxide (TMAOH) for Methane (CH4 ) and Carbon Dioxide (CO2 ) gas hydrates. TMAOH belongs to ammonium based ionic liquids (AILs) which is comparatively economical ILs among the other ILs families. Traditional T-cycle technique with isochoric step heating method was adopted for determining thermodynamic inhibition in this work. Results reveal that TMAOH effectively shift the hydrate equilibrium curve to upper pressure and lesser temperature regions for CH4 + TMAOH + water system and CO2 + TMAOH + water system. The average reduced temperature obtained for CH4 + TMAOH + water system is around 1.06 o C while for CO2 + TMAOH + water system, the inhibition effect found to be around 2.09 o C. Therefore, this study provides roadmap for superior alternative for the development of novel thermodynamic hydrate inhibitor, which can efficiently control the gas hydrate formation.